Inclusion and aesthetic accessibility (Revista de Ensino em Artes, Moda e Design, 2024)
This article presents an analysis on inclusion and aesthetic accessibility in museums and exhibitions, taking as a starting point the obstacles for people with disabilities between their home journey and the visit to a museum exhibition. To do so, it is based on what is meant by a modern city, with references to the Haussmann Reform in Paris, the Pereira Passos Reform in the city of Rio de Janeiro, Francisco Prestes Maia's avenue plan for the city of São Paulo and the renovation designed by Michell Whitley and Douglas Fox for Recife, the capital of Pernambuco. This analysis continues with a case study on accessibility at the Museu do Ipiranga after the reopening, which made it more inclusive, and ends with reflections on what aesthetic accessibility is.
Keywords: inclusion; accessibility; aesthetic